Single-cell RNA-seq reveals aberrant airway epithelial- immune cell crosstalk in pulmonary fibrosis - Hewitt,R; Chakravarty,P; Perez-Lloret,J; Banchero,M; Berg,M; van,den Berge M; Traves,W; Yates,L; Walker,S; Gaboriau,D; Rice,A; Nicholson,A; et al. (ERJ Open Research, 2025)
BackgroundEpithelial-immune cell interactions are crucial in the regulation of pulmonary immune responses. Emerging evidence suggests that cell populations lining the airways may play a pivotal role in the pathogenesis of idiopathic pulmonary fibrosis (IPF), a disease characterised by progressive scarring of the lung parenchyma. We profiled the cellular landscape of the airway mucosal niche in incident cases of IPF to understand early-stage events contributing to disease development.MethodsSingle-cell RNA-sequencing was used to explore cellular heterogeneity in proximal airway brushings from seven healthy controls and nine patients with newly diagnosed IPF. In-depth bioinformatics analysis was used to interrogate changes in cell populations and cell-cell communication in IPF patients compared to controls.ResultsWe show a relative increase in the abundance of airway macrophage subsets in IPF compared to healthy controls, and disease-specific changes in their transcriptional profile. Increased frequency of airway macrophages and proliferating macrophages was associated with more extensive disease at baseline quantified by the composite physiological index and radiological severity of traction bronchiectasis. Monocyte-derived macrophages were significantly enriched at baseline in IPF patients who had disease progression at 12months. Using CellChat we exposed differences in cell-cell communication between airway epithelial cells, airway macrophages and T cells in IPF. We identified dysregulation in signalling pathways such as SEMA3, ANXA1 and DESMOSOME which modulate airway epithelial-macrophage interactions, potentially driving disease pathology.ConclusionsAirway epithelial cells and macrophages may play a key role in orchestrating the early immunopathology of IPF, and these data support further exploration of novel, airway-focused therapeutic targets in IPF.